Quality of Life in Patient with Acne Vulgaris - Shrestha, Pratistha; Shrestha, Meera; Gurung, Sabhyata; Chhetri, Pradip; Poudyal, Yogesh (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Acne Vulgaris is one of the common skin disease which can impair the quality of life of the individual. This study is done to assess the quality of life in patient with acne using Dermatology life quality index (DLQI) and Cardiff acne disability index (CADI). MATERIAL AND METHODS This was a cross-sectional, questionnaire-based study in 101 patients of acne vulgaris at dermatology and Venerology OPD of Universal College of Medical Science, Bhairahawa, Nepal. The participants were given DLQI and CADI to assess the quality of life. The severity of acne was assessed by simple grading system. RESULTS There was some effect in quality of life in patient with acne but there was no signiﬁcant relation with severity of acne and quality of life. CONCLUSION Psychological assessment should be done in patient with acne vulgaris as it can have negative effect in quality of life.